Venous thromboembolism incidence in the Ireland east hospital group: a retrospective 22-month observational study. Issue 6 (21st June 2019) - Kevane, Barry; Day, Mary; Bannon, Noirin; Lawler, Leo; Breslin, Tomas; Andrews, Claire; Johnson, Howard; Fitzpatrick, Michael; Murphy, Karen; Mason, Olivia; O'Neill, Annemarie; Donohue, Fionnuala; et al.
Abstract : Objectives: To determine the incidence of venous thromboembolism (VTE) and the incidence of hospital-acquired VTE (HA-VTE) arising within the population served by the Ireland East Hospital Group (IEHG). Design: /home/user/Documents/Sathish Kumar G/RFO/June/21-06-2019/bmjopen_iss_9_7_20190621_1/ A retrospective observational study was conducted using hospital discharge data obtained from the hospital inpatient enquiry data reporting system. In this system, VTE events recorded as 'primary diagnosis' represented the reason for initial hospital admission, whereas VTE recorded as a 'secondary diagnosis' occurred following admission and were therefore used as an approximation of HA-VTE. These data were used to estimate the overall incidence of VTE and the proportion of these events which were hospital-acquired. Setting: The IEHG is the largest hospital group in the Irish healthcare system and serves a population of over 1 million individuals. Participants: Data were generated from records pertaining to the 2727 patient admission episodes where a diagnosis of VTE was made during the 22-month study period. Results: During the study period, 2727 VTE events were recorded within the IEHG (which serves a population of 1 036 279) corresponding to an incidence of 1.44 (95% CI 1.36 to 1.51) per 1000 per annum. 1273 (47%) of VTE events were recorded as secondary VTE. The incidence of VTE was highest among individuals over 85 years of age (16.03 per 1000;95% CI 12.81 to 19.26) and was more common following emergency hospital admission. Conclusion: These data suggest that HA-VTE accounts for at least 47% of all VTE events arising within a hospital group serving a population of over 1 million individuals within the Ireland. Given that HA-VTE is a well-recognised source of (potentially preventable) hospital deaths, these findings provide a compelling argument for prioritising strategies directed at reducing the risk of VTE among hospital patients served by the IEHG and within the Ireland as a whole.